2013
DOI: 10.1111/aos.12011
|View full text |Cite
|
Sign up to set email alerts
|

Oximetry in glaucoma: correlation of metabolic change with structural and functional damage

Abstract: ABSTRACT.Purpose: To determine whether retinal vessel oxygen saturation in patients with glaucoma is associated with structural optic disc and retinal nerve fibre layer (RNFL) changes and visual field (VF) defects. Methods: Fifty-nine patients with confirmed glaucoma were recruited at University Hospitals Leuven. Retinal oxygen saturation in patients with glaucoma was measured with a noninvasive spectrophotometric retinal oximeter (Oxymap ehf, Reykjavik, Iceland). VF and Heidelberg retinal tomographies (HRTs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
109
3
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(126 citation statements)
references
References 31 publications
13
109
3
1
Order By: Relevance
“…These average SO 2 values are lower than those found in our study ( Table 2) and that reported previously (69% and 65% in severe and mild glaucoma, respectively). 17 However, the clinical conclusion drawn from the studies remains the same regardless of variation in average SO 2 values.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…These average SO 2 values are lower than those found in our study ( Table 2) and that reported previously (69% and 65% in severe and mild glaucoma, respectively). 17 However, the clinical conclusion drawn from the studies remains the same regardless of variation in average SO 2 values.…”
Section: Discussionmentioning
confidence: 84%
“…These results are in agreement with outcomes from previous studies that have investigated retinal SO 2 in patients with glaucoma using different techniques. 16,17 A complex of clinical factors contributing to the pathophysiology of glaucomatous optic neuropathy, including altered retinal blood flow and ischemia, has made the use of retinal oximetry a potentially important clinical tool in the diagnosis of glaucoma. Michelson and Scibor 10 reported significantly lower arterial oxygen saturation in patients with normal tension glaucoma (NTG) compared to healthy controls (89.7% ± 5.4% vs. 92.3% ± 3.4%) and reported a significant association with glaucomatous optic rim damage in more advanced glaucoma.…”
Section: Discussionmentioning
confidence: 99%
“…We recently reported abnormalities in retinal oxygen metabolism in patients with advanced glaucomatous visual field defects,4 and with decreasing neuroretinal rim area of the optic disc as well as nerve fibre layer thinning 5. These studies were performed with non-invasive spectrophotometric retinal oximetry6 7 and indicated increased haemoglobin oxygen saturation in retinal venules in glaucomatous eyes with advanced visual field defects compared with those with mild visual defects.…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary studies have shown impaired SaO 2 in glaucomatous eyes, especially in advanced stages, compared with normal eyes 12–14. Impaired retinal oxygen metabolism has also been associated with deeper glaucomatous VF defects,15 decreased neuroretinal rim area and RNFL thinning 16. These findings suggest that altered retinal oxygen metabolism in glaucomatous eyes may be associated with structural damage 16…”
Section: Introductionmentioning
confidence: 99%